Spatial, spectral, and time-resolved characterization of single upconverting particles for micro- and nanothermometry - SILVA, Allison Rodrigo Pessoa da (2022)
The scientific community is increasingly looking deeper at phenomena in the micro and nanoscale. The miniaturization of electronic circuitry, biological and medical tools, and com- munication devices demands investigations at this level. Particularly, sensing temperature at submicron scales is crucial to analyzing numerous physical-chemical processes. To this end, lanthanoid ions doped in solid-state matrices are of special interest because of their unique optical properties. However, to indeed achieve high spatial resolutions, the single-particle mea- surement level must be employed, which brings many physical and instrumental artifacts that can disturb the thermal response of such systems. This work aims to characterize experi- mentally and theoretically single particles of NaYF4: Yb3+/Er3+ as thermometers and also to investigate the role of physical and instrumental parameters affecting the measurement readouts. The experimental investigations involved spectral measurements, Scanning Probe Microscopy characterization, and luminescence time-resolved analysis. In particular, the hy- perspectral imaging technique is employed to investigate the thermal response of different groups of ions inside a single particle. Computationally, it is employed algorithms to simulation the electronic population dynamics during light-matter interaction. This allows to test and further predict the behavior of lanthanoid systems to thermometry. The results discussed in this work can help understand more closely the internal and external factors interfering with the reliability of single micro and nanothermometers and establish a new method of surface effects analysis.